2017
DOI: 10.1021/acs.inorgchem.7b01210
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of the Reversible Chemical Reduction and Reoxidation of Substitutional Cr Ions in Sr2TiO4

Abstract: The solid-state synthesis and controllable speciation of Cr dopants in the layered perovskite SrTiO is reported. We employed a chemical reduction procedure with NaBH at relatively mild temperatures (<450 °C) to impart sensitive control over the relative concentration of Cr dopants, the charge-state of oxygen-vacancy defects, and presence of Ti defects in highly reduced Cr-doped SrTiO. The electron paramagnetic resonance (EPR) spectra of the reduced powder samples reveal a 12-fold increase in the Cr concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…28 Previously, some of us demonstrated the introduction of Ti 3+ defects could also be achieved in bulk Cr 3+ -doped SrTiO 3 (and related Sr 2 TiO 4 ) powders using NaBH 4 . 36,37 After this chemical reduction, the Cr 3+ concentration increases by an order of magnitude according to quantitative EPR measurements because of the reduction of EPR-silent Cr species to Cr 3+ prior to formation of Ti 3+ defects. No such increase in the Cr 3+ EPR signal is observed at the start of photodoping (see the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…28 Previously, some of us demonstrated the introduction of Ti 3+ defects could also be achieved in bulk Cr 3+ -doped SrTiO 3 (and related Sr 2 TiO 4 ) powders using NaBH 4 . 36,37 After this chemical reduction, the Cr 3+ concentration increases by an order of magnitude according to quantitative EPR measurements because of the reduction of EPR-silent Cr species to Cr 3+ prior to formation of Ti 3+ defects. No such increase in the Cr 3+ EPR signal is observed at the start of photodoping (see the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In II–VI semiconductors quantum dots (QDs), incorporation of a dopant metal ion with the same charge (i.e., Mn­(II), Cr­(II), and Co­(II)) leads to simple substitutional incorporation of the ion of interest up to its solubility limit. Incorporation of an ion that has a different charge, such as Cu­(I), Cr­(III), Eu­(III), Fe­(III), or Al­(III), results in formation of ion vacancies in the QD in order to reach charge neutrality, or in a rare case formation of ZnCr 2 Se 4 spinel inclusion inside Cr­(III)-doped ZnSe QDs . The unusual phase segregation in the 2D Mn:CsPbCl 3 NPLs could be understood by the flexible continuum model by considering the effects of coherency strains as well as the gradient energy term in the crystal lattice. , The strain is more significant with high Mn doping concentrations considering the large size mismatch (>30%) between the Mn 2+ (97 pm) dopant and the Pb 2+ (133 pm).…”
Section: Discussionmentioning
confidence: 99%
“…We previously studied the effect of a relatively low-temperature NaBH 4 reduction reaction on the oxidation state of Cr dopants in SrTiO 3 and related Sr 2 TiO 4 bulk powders (Lehuta and Kittilstved, 2016; Lehuta et al, 2017). In those studies, we observed an order of magnitude increase in the Cr 3+ concentration by EPR spectroscopy that we attributed to the reduction of EPR-silent high-valent Cr 4+ and Cr 6+ ions.…”
Section: Introductionmentioning
confidence: 99%